2015
DOI: 10.1007/s00442-015-3536-7
|View full text |Cite
|
Sign up to set email alerts
|

Population limitation in a non-cyclic arctic fox population in a changing climate

Abstract: Arctic foxes Vulpes lagopus (L.) display a sharp 3- to 5-year fluctuation in population size where lemmings are their main prey. In areas devoid of lemmings, such as Iceland, they do not experience short-term fluctuations. This study focusses on the population dynamics of the arctic fox in Iceland and how it is shaped by its main prey populations. Hunting statistics from 1958-2003 show that the population size of the arctic fox was at a maximum in the 1950s, declined to a minimum in the 1970s, and increased st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 39 publications
3
46
2
Order By: Relevance
“…However, taking these differences into account, there were also similarities in demographic response and especially in the carrying capacity. Pálsson et al (2016) reported changes in many Icelandic bird populations that are included in the Arctic fox diet. So these changes are likely the major component in the carrying capacity for Icelandic Arctic foxes.…”
Section: Coastal and Inland Populationsmentioning
confidence: 96%
See 4 more Smart Citations
“…However, taking these differences into account, there were also similarities in demographic response and especially in the carrying capacity. Pálsson et al (2016) reported changes in many Icelandic bird populations that are included in the Arctic fox diet. So these changes are likely the major component in the carrying capacity for Icelandic Arctic foxes.…”
Section: Coastal and Inland Populationsmentioning
confidence: 96%
“…The hunting statistics of Arctic foxes in Iceland, collected by the Environment Agency of Iceland and its predecessor, the Wildlife Management Institute, suggest that the Arctic fox population in Iceland declined from the late 1950s until the 1970s, whereafter the population has been on the increase. The causes of this fluctuation have been related to changes in prey populations as well as climate, but the hunting effort is considered to have been stable during this period (Pálsson et al 2016). Such factors can directly affect birth and mortality rates and would be of central importance for understanding and managing the Arctic fox population.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 3 more Smart Citations